WRITING AUDIT ON PUTREFY IN FRIENDLY ORGANIZATION AND PRIMARY DRIVER - Bandula Abeysekera (International Scientific and Current Research Conferences, 2021)
The worldwide development towards social and financial arrangement changes has not generally created the outcomes that were required from it. Not rarely, strategy changes have prompted financial downturn, political mayhem and social deterioration. Accepting Sri Lanka as a contextual analysis, we have inspected the course of monetary changes and its communication with socio-political organizations, asking how liberal financial changes produce the outcomes they did in this particular setting. The voluminous writing that exists on Sri Lankan monetary arrangement accepts, nearly as per normal procedure, that resulting socio-political rot has had nothing anything that to do with its financial changes. It has kept down its helpful impacts.